The public perception on persuasive power by influential public figures on surname for Muslim child born out of wedlock / Safiah Nur Atikah Roslan - Roslan, Safiah Nur Atikah (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2018)
In July 2017, Malaysia's Court of Appeal has granted the appeal made by parents of a seven (7) years old male child who was born only five (5) months and 24 days from the date his parents were legally married to be given the patronymic surname of his biological father instead of 'Abdullah'. Attentively, the Judge of Court of Appeal, Datuk Abdul Rahman Sebli, in his jurisdiction has aforementioned that the surname 'Abdullah' registered to the name of the child will cause difficulties to the child in future as there is stigma attached to the surname 'bin Abdullah' for a Muslim born child he is. The decision made by the Court of Appeal, however, has brought forward various reactions from many individuals. Those individuals include Mufti Perlis as well as lawyer cum human rights' activist, Siti Kasim whom have provided the public with opinions that were deem rather odd in regards to the case discussed and thus, it has created a polemic and arguments amongst the public. Hence, this paper is studying the confusions Malay Muslims had in regards to the issue of surname given to Muslim children born out of wedlock, the persuasive power of the two individual mentioned earlier and the differences in opinions between Muslim "conservatives" and "liberals". This is an applied exploratory research in which the case being studied is a deviant case and it was conducted through a qualitative method. The findings have shed a new light on Malaysians' cognitive maturity in giving weightage to the pros and cons of this issue.